Santos y obispos en la Siria tradorromana. La historia Philotheos de Teodoreto de Cirros y la construcción del monacato oriental - Francisco, Héctor (Byzantion Nea Hellás, 2015)
This paper explores the ideological and political implications of the Late Antique Hagiography through the study of one of the main works of Late Antique hagiographical Literature, the Historia Religiosa written by Theodoretus of Cirrhus. This collection of biographies of Syrian hermits has a central place in the construction of the Byzantine monastic tradition by including the ancient ascetical patterns of the semitical Christianity of Syria and Mesopotamia into the monastic movement whose models are Egypt and Capadocia. The author, a hellenized bishop of northern Syria, outlines his own monastic ideal through the stories of the main figures of the Syriac ascetical movement. In so doing, the Historia Religiosa not only describes the origins of monasticism but also translates it according to the ideal of the Helenized Church. The monastic movement, and the cult around it, is related to the construction of a new hierarchical structure within the Church. Thus, the Imperial Church´s main goal is to “domesticate” the anarchic Christian ascetical models developed in the first three centuries of the Church and moderate the excentric ways of mortification. The aim of this paper is to offer a complementary view of the sociological or structural the origins of the cult of the saints and the evolution of eastern Christian spirituality.